Negotiating Religious Authority: Patronage Networks and the Social Practice of Lunar Month Determining at Pesantren Cokrokertopati Takeran - Asih Pertiwi; Agus Nurhadi; M. Syaoqi Nahwandi; Dessy Asnita (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2025)
The criteria for determining the beginning of the hijri month in Indonesia continue to develop; however, Pesantren Cokrokertopati Takeran continues to maintain the use of classical method that does not significantly differ in outcome from the goverment’s official determination. This study does not aim merely to examine the astronomical aspect; but rather to analyze the socio-religious practices that sustain its continued application within the community. Employing a qualitative approach through in-depth interviews, this study seeks to explain why the methode remains authoritative and why the community tends to follow religiuous leadership rather than state-based decisions. The findings reveal that the practice of determining the beginning of the hijri month at Pesantren Cokrokertopati Takeran is shaped by long-established patron-client relationships beetween religious leaders and community members, grounded in the exchange of religious values, trust, and moral legitimacy. Furthermore, Pesantren Cokrokertopati’s position as an independent institution, unaffiliated with any formal religious organization, reinforce its social credibility and authoruty in religious decision-making, including determinaton of the hijri calendar. This study therefore affirms that the determination of the beginning of the hijri month at Pesantren Cokrokertopati Takeran represenst a form of social falak, in which social and religious dimensions play a more dominant role than purely technical-astronomical considerations.